Field effect and applications - Bueno, Paulo Roberto [UNESP] (My University, 2018)
Chapter 1 discussed the importance of establishing a unified standpoint for electronics and electrochemistry, and also showed that this can be done by suitably defining chemical or electrochemical capacitances. In Chap. 2, a detailed description was given about how chemical or electrochemical capacitances (if an electrolyte is considered in the analysis) can be derived using the first principles of quantum mechanics.